(untitled) (Swiss Medical Weekly, 2011)
OBJECTIVES: Despite a broad and efficient pharmacological antihypertensive armamentarium, blood pressure (BP) control is suboptimal and heterogeneous throughout Europe. Recent representative data from Switzerland are limited. The goal of the present survey was therefore to assess the actual control rate of high BP in Switzerland in accordance with current guidelines. The influence of risk factors, target organ damage and medication on BP levels and control was also evaluated. METHODS: A cross-sectional visit-based survey of ambulatory hypertensive patients was performed in 2009 in Switzerland. 281 randomly selected physicians provided data on 5 consecutive hypertensive patients attending their practices for BP follow-up. Data were anonymously collected on demographics, comorbidities and current medication, and BP was recorded. Subsequent modification of pharmacological antihypertensive therapy was assessed. RESULTS: Data from 1376 patients were available. Mean age was 65 ± 12 years, 53.9% were male subjects. 26.4% had complicated hypertension. Overall, BP control (<140/90 mm Hg for uncomplicated and <130/80 mm Hg for complicated hypertension) was achieved in 48.9%. Compared to patients with complicated hypertension, BP control was better in patients with uncomplicated hypertension (59.4% vs. 19.2%, p <0.001). As a monotherapy the most prescribed drug class were angiotensin receptor blockers (ARB, 41%), followed by angiotensin converting enzyme (ACE) inhibitors (21.5%), betablockers (20.8%) and calcium channel blockers (CCB, 10.8%). The most prescribed drug combinations were ARB + diuretic (30.1%) and ACE inhibitors + diuretic (15.3%). 46% were receiving a fixed drug combination. In only 32.7% of patients with uncontrolled hypertension was a change in drug therapy made. CONCLUSION: This representative survey on treated adult hypertensive patients shows that, compared to earlier reports, the control rate of hypertension has improved in Switzerland for uncomplicated but not for complicated, particularly diabetes-associated hypertension. ARBs and ACE inhibitors are the most prescribed antihypertensive drugs for monotherapy, whereas diuretics and ARBs were the most used for combination therapy.